Improving Use Case Specifications by Means of Refactoring - Marcos, Claudia Andrea (2015)
This work presents a semi-automatic tool for use case refactoring called RE-USE. This tool discovers existing quality problems in use cases and suggests a prioritized set of candidate refactorings to functional analysts. The analyst then reviews the recommendation list and selects the most important refactoring. The tool applies the chosen refactoring and returns an improved specification. The tool effectiveness in detecting existing quality problems and recommending proper refactorings was assessed using a set of case studies related to real-world systems obtaining encouraging results.